Advocacy of advance care planning by social ecological model in Taiwan. Issue 1 (1st June 2011) - Chen, Y R; Wang, N; Wang, Y W
Abstract : The National Health Insurance in Taiwan started to reimburse for non-cancer diagnoses like congestive heart failure, COPD, end stage renal disease since 1st September 2009, the driving of advance care planning not only can encourage terminal patients to think about the meaning of life, but also help chronic illness patients to understand the mode of palliative care treatment at the early stage, so that we can improve the quality of care and the dignity of patients in final stage. Objectives: (1) To encourage public to think about the issues of live and death earlier through the driving of advance care of planning. (2) Palliative care can intervention every medical treatment in early stage, so we can efficiently improve and implement the quality of care for terminal patients. Methods: (1) This program is driven by the social ecological model. (2) Methods of implementation include: ▶ Design ACP promotion flyers for hospitals and public promotion activities. ▶ Make an ACP advertisement and the official website of Hospice Foundation of Taiwan ▶ To host the public promotion activities. Conclusion: In 2010, the goals of this program are to make an advertisement, to design the promotion flyers for Advance Care Planning, and to host 41 public promotion activities for over 2400 people. To respect the medical autonomy of terminal patients and reduce the medical futility, we will not only hosting public promotion activities and clinical training courses, but also will drive this plan on related medical policy.